2008
DOI: 10.1523/jneurosci.1283-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Arx Is a Direct Target of Dlx2 and Thereby Contributes to the Tangential Migration of GABAergic Interneurons

Abstract: The Arx transcription factor is expressed in the developing ventral telencephalon and subsets of its derivatives. Mutation of human ARX ortholog causes neurological disorders including epilepsy, lissencephaly, and mental retardation. We have isolated the mouse Arx endogenous enhancer modules that control its tightly compartmentalized forebrain expression. Interestingly, they are scattered downstream of its coding region and partially included within the introns of the downstream PolA1 gene. These enhancers are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
127
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(134 citation statements)
references
References 60 publications
6
127
0
Order By: Relevance
“…Previous work has shown that Dlx1/2 activity induces the expression of the transcription factor Arx (Cobos et al, 2005a;Colasante et al, 2008), promoting migration by suppressing neurite growth mediated by Pak3, a p21-activated serine/ threonine kinase that acts as a downstream effector of the Rho family of GTPases (Cobos et al, 2007). However, in our microarray analysis comparing gene expression levels in control versus Prox1 loss-of-function cells, we did not reveal any measurable change in Pak3, Arx, or any of the Dlx-gene family members (data not shown).…”
Section: Loss Of Prox1 Results In Dysregulation Of Relatively Few Genmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous work has shown that Dlx1/2 activity induces the expression of the transcription factor Arx (Cobos et al, 2005a;Colasante et al, 2008), promoting migration by suppressing neurite growth mediated by Pak3, a p21-activated serine/ threonine kinase that acts as a downstream effector of the Rho family of GTPases (Cobos et al, 2007). However, in our microarray analysis comparing gene expression levels in control versus Prox1 loss-of-function cells, we did not reveal any measurable change in Pak3, Arx, or any of the Dlx-gene family members (data not shown).…”
Section: Loss Of Prox1 Results In Dysregulation Of Relatively Few Genmentioning
confidence: 98%
“…However, aside from transcription factors, Dlx, Arx, and CoupTF, which participate in the early development of both MGE and CGE cortical interneuron subtypes (Cobos et al, 2005b;Colasante et al, 2008;Friocourt et al, 2008;Kanatani et al, 2008;Lodato et al, 2011), a distinct genetic cascade that regulates CGE-derived cortical interneuron development has not yet been characterized.…”
Section: Within Cortical Interneuron Lineages Prox1 Expression Is Sementioning
confidence: 99%
See 1 more Smart Citation
“…If no defect is observed, it is possible that Re1 might play a redundant role in mediating Arx transcription in developing islet ␣-cells. Outside of the pancreas, Arx expression is also detected in the developing ventral telencephalon of the brain, where its expression is directly regulated by the homeodomain factor Dlx2 (37,38). Two Dlx2 binding sites (HD-1 and HD-2) have been identified in the highly conserved noncoding sequence of the Arx locus (referred to as mUAS3, 37), which encompasses the Re2 sequences.…”
Section: Discussionmentioning
confidence: 99%
“…ARX is an extremely important gene in cortical development as ARX regulates genes involved in cell migration, axonal guidance, neurogenesis, and transcription regulation (Colombo et al 2007;Colasante et al 2008Colasante et al , 2013Fulp et al 2008;Okazaki et al 2008), although the mechanisms are not yet known. Because ARX interacts with many different targets during development, mutations cause a wide range of abnormalities, including mental retardation (syndromic and nonsyndromic), infantile spasms without brain malformations, dyskinesia, agenesis of the corpus callosum with abnormal genitalia, variant lissencephaly with dys- morphic basal ganglia, and hydranencephaly (Kato et al 2004;Okazaki et al 2008).…”
Section: Malformations Of Cortical Development and Epilepsymentioning
confidence: 99%